2016
DOI: 10.2147/ott.s77828
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological significance of <em>RUNX3</em> hypermethylation and mRNA expression in human breast cancer, a meta-analysis

Abstract: Aberrant promoter methylation of RUNX3 has been reported in several tumors including human breast cancer (BC). However, the association between RUNX3 hypermethylation and incidence of BC remains elusive. In this study, a detailed literature search was performed in Medline and Google Scholar for related research publications. Analysis of pooled data were executed. Odds ratios with corresponding confidence intervals were determined and summarized, respectively. Finally, 13 studies were identified for the meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Human Runt-related transcription factor 3 (RUNX3) is a negative regulatory gene of malignant tumors whose abnormal expression is closely related to various human malignant tumors. For example, RUNX3 expression has been reported to be down-regulated in gastric cancer, 19 liver cancer, 20 breast cancer, 21 adenoid cystic carcinoma [22][23][24] and other tumor tissues, and indicated poor prognosis. Prior in vitro experiments showed that overexpression of RUNX3 could induce tumor cell apoptosis while inhibiting proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Human Runt-related transcription factor 3 (RUNX3) is a negative regulatory gene of malignant tumors whose abnormal expression is closely related to various human malignant tumors. For example, RUNX3 expression has been reported to be down-regulated in gastric cancer, 19 liver cancer, 20 breast cancer, 21 adenoid cystic carcinoma [22][23][24] and other tumor tissues, and indicated poor prognosis. Prior in vitro experiments showed that overexpression of RUNX3 could induce tumor cell apoptosis while inhibiting proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%